Collective Dynamics and Transient Behavior of Partially Hydrophobic Hyaluronic Acid Chains. Issue 2 (29th November 2013) - Finelli, Ivana; Chiessi, Ester; Oddo, Letizia; Galesso, Devis; Renier, Davide; Paradossi, Gaio
<x xml:space="preserve">Abstract</x> The unique performance of a partially hydrophobic derivative of hyaluronic acid, HYADD4, bearing 2–3 hexadecylic side chains every 100 repeating units, enables hydrogels based on this polymer to be suitably used as a viscosupplement to replace synovial fluid in stressed or injured articular joints. This contribution addresses: i) as to whether there is a self‐assembly process driving the HYADD4 hydrogel stabilization and ii) what the characteristics of the long‐range dynamics governing the macroscopic viscoelastic behavior are, and to what extent these features are different from those present in the parent polymer (i.e., hyaluronic acid). Mesoscale dynamic and static properties are interpreted in the light of "sticky reptation theory" and evaluated in combination with small‐angle neutron scattering results. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>